Holly Solomon Gallery: The First Two Years. - Holly Solomon Gallery, New York (New York : Holly Solomon Gallery, 1977)
Davis, Brad ; Shostak, Ed ; Nonas, Richard ; MacConnel, Kim ; Lanigan-Schmidt, Thomas ; Schneeman, George ; Bark, Jared ; Highstein, Jene ; Kushner, Robert ; Smyth, Ned ; Cady, Sam ; Matta-Clark, Gordon ; Heilmann, Mary ; Harris, Suzanne ; Johns, Jerry ; etc.
Engels
boek